Integrasi Moral Agama dalam Pendidikan Budi Pekerti di Madrasah Tsanawiyah Pondok Pesantren Tri Bhakti At-Taqwa Lampung Timur Indonesia - Nurul Wahida; Agung Lestiono; Dwi Puspita Sari; Evi Verliantika; Banon Ferdiana; Ikhwan Aziz Q; Andika Ari Saputra (KURAS Institute, 2022)
In today’s modern era, moral decline has reached a concerning level across all age groups, from children to adults. Core moral values such as honesty, truth, and justice essential components of religious teachings are increasingly fading. Thus, moral education in schools must be implemented earnestly. This study aims to explore the integration of religious moral values in character education for Grade VIII students at Madrasah Tsanawiyah Pondok Pesantren Tri Bhakti At-Taqwa Rama Puja, North Raman, East Lampung. Using a qualitative descriptive approach and field research methods, data were collected through observation, interviews, and documentation, and analyzed inductively. The findings reveal two main strategies for integrating religious morals: (1) habituation, also known as character building, to instill consistent moral behavior, and (2) modeling, where students emulate the attitudes and behaviors of exemplary figures. Moral values embedded in the Akidah Akhlak subject include praiseworthy traits such as humility (tawādu’), contentment (qanā‘ah), patience (ṣabr), honesty (ṣidq), tolerance (tasāmuḥ), cooperation (ta’āwun), sincerity (ikhlāṣ), and justice (‘adl).